PERANCANGAN PROTOTIPE APLIKASI PERUMAHAN TAMAN KENARI SENSOR MONITOR MENGGUNAKAN METODE AGILE - Abdurrachman, Ichramsyah; Gita Purnama, Diki (ITP Press, 2024)
Taman Kenari Housing Complex is a residential area located in Bogor Regency, West Java. The complex is relatively quiet during the day, evening, and night, which can lead to security issues for the homes. One of the problems faced by the residents of Taman Kenari Housing Complex is the lack of effective monitoring and supervision of their home security. To address this issue, the author designed a prototype application called Taman Kenari Sensor Monitor using the Agile method. The purpose of this study is to design the Taman Kenari Sensor Monitor prototype as an effective solution to enhance the security and efficiency of home monitoring in the Taman Kenari Housing Complex. Through this prototyping approach, the Taman Kenari Sensor Monitor application can be visually represented in the form of a mockup that meets user needs while being efficient in terms of functionality and aesthetics. The prototype is designed using UML (Unified Modeling Language) modeling and implemented in the form of a mockup created in Figma. Application testing was carried out using the Blackbox method to test the overall functionality of the application. This study provides a structured solution to address the home security issues in the Taman Kenari Housing Complex.